DeView: Confining Progressive Web Applications by Debloating Web APIs - Oh, ChangSeok; Lee, Sangho; Qian, Chenxiong; Koo, Hyungjoon; Lee, Wenke (38th Annual Computer Security Applications Conference (ACSAC 2022), 2022)
A progressive web application (PWA) becomes an attractive option for building universal applications based on feature-rich web application programming interfaces (Web APIs). While flexible, such vast APIs inevitably bring a significant increase in an API attack surface, which commonly corresponds to a functionality that is neither needed nor wanted by the application. A promising approach to reduce the API attack surface is software debloating, a technique wherein an unused functionality is programmatically removed from an application or API. Unfortunately, debloating PWAs is challenging, given the monolithic design and non-deterministic execution of a modern web browser. In this paper, we present DeView, a practical approach that reduces the attack surface of a PWA by blocking unnecessary but accessible web APIs. DeView tackles the challenges of PWA debloating by i) record-and-replay web API pro- filing that identifies needed web APIs on an app-by-app basis by replaying (recorded) browser interactions and ii) compiler-assisted browser debloating that eliminates the entry functions of corresponding web APIs from the mapping between web API and its entry point at a binary level. Our evaluation shows the effectiveness and practicality of DeView. DeView successfully eliminates 91.8% of accessible web APIs while i) maintaining original functionalities and ii) preventing 76.3% of known exploits on average.